Comparison of Hamstrings and Quadriceps Femoris Muscle Thickness Increment between Agonist-Antagonist Paired Set and Traditional Set Resistance Training in Untrained Healthy Subjects - Gutama Arya Pringga; R. A. Meisy Andriana; Indrayuni Lukitra Wardhani; Lydia Arfianti (Surabaya Physical Medicine and Rehabilitation Journal, 2021)
Background: Resistance training is an effective way to increase muscle mass. Resistance training with agonist-antagonist paired set method can be an alternative to increase muscle mass within a relatively short training time.Aim: To compare the increase in hamstrings and quadriceps femoris muscle thickness between agonist-antagonist paired set (APS) and traditional set (TS) resistance training in untrained healthy subjects.Material and Methods: This study was an experimental study on 16 untrained healthy men which were randomly assigned to the APS and the TS group. Each group got leg curl and leg extension exercises with equal training volume for 6 weeks. For the APS group, 1 set of leg curls was followed by 1 set of leg extensions, repeated for 3 sets. For the TS group, 3 sets of leg curls were followed by 3 sets of leg extensions. Muscle thickness was compared from pre- to post-training and between the intervention groups using B-mode ultrasound.Results: Muscle thickness of the hamstrings and quadriceps femoris increased significantly from pre- to post-training in both groups (p<0.05). The increase in muscle thickness between the two groups was not significantly different (p> 0.05).Conclusion: Resistance training with the APS method did not give a higher increment of hamstrings and quadriceps femoris muscle thickness compared to the TS method in healthy untrained subjects.